MYB30 integrates light signals with antioxidant biosynthesis to regulate plant responses during postsubmergence recovery. Issue 6 (9th January 2023) - Xie, Li‐Juan; Wang, Jian‐Hong; Liu, Hui‐Shan; Yuan, Li‐Bing; Tan, Yi‐Fang; Tan, Wei‐Juan; Zhou, Ying; Chen, Qin‐Fang; Qi, Hua; Li, Jian‐Feng; Chen, Yue‐Qin; Qiu, Rong‐Liang; et al.
Summary: Submergence is an abiotic stress that limits agricultural production world‐wide. Plants sense oxygen levels during submergence and postsubmergence reoxygenation and modulate their responses. Increasing evidence suggests that completely submerged plants are often exposed to low‐light stress, owing to the depth and turbidity of the surrounding water; however, how light availability affects submergence tolerance remains largely unknown. Here, we showed that Arabidopsis thaliana MYB DOMAIN PROTEIN30 (MYB30) is an important transcription factor that integrates light signaling and postsubmergence stress responses. MYB DOMAIN PROTEIN30 protein abundance decreased upon submergence and accumulated during reoxygenation. Under submergence conditions, CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1), a central regulator of light signaling, caused the ubiquitination and degradation of MYB30. In response to desubmergence, however, light‐induced MYB30 interacted with MYC2, a master transcription factor involved in jasmonate signaling, and activated the expression of the VITAMIN C DEFECTIVE1 ( VTC1 ) and GLUTATHIONE SYNTHETASE1 ( GSH1 ) gene families to enhance antioxidant biosynthesis. Consistent with this, the myb30 knockout mutant showed increased sensitivity to submergence, which was partially rescued by overexpression of VTC1 or GSH1 . Thus, our findings uncover the mechanism by which the COP1‐MYB30 module integrates light signals with cellular oxidative homeostasis to coordinate plant responses to postsubmergence stress.